2021
DOI: 10.1039/d0sc06295b
|View full text |Cite
|
Sign up to set email alerts
|

Switch chemistry at cryogenic conditions: quantum tunnelling under electric fields

Abstract: Adding an external electric field to reactions driven by quantum mechanical tunneling brings a whole new dimension to the idea of switch chemistry.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 88 publications
(151 reference statements)
0
29
0
Order By: Relevance
“…Works on catalysis have appeared, in which, instead of a material catalyst, the influence of an external electric field on the acceleration of chemical reactions is studied [15][16]. In them, the acceleration of the reaction occurs without a catalyst only under the action of an electric field.…”
Section: External Electromagnetic Field and Electrons As A Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Works on catalysis have appeared, in which, instead of a material catalyst, the influence of an external electric field on the acceleration of chemical reactions is studied [15][16]. In them, the acceleration of the reaction occurs without a catalyst only under the action of an electric field.…”
Section: External Electromagnetic Field and Electrons As A Catalystmentioning
confidence: 99%
“…Recent studies have revealed a new type of physical influence on chemical reactions with the help of an external electric field, which is considered as a physical catalyst or pseudocatalyst [15,24]. But since the field is not a reactant, not a product and not even a substance [15], the IUPAC formulation is also not a universal definition of a catalyst. The field, as a catalyst or pseudocatalyst, is outside the scope of this IUPAC definition.…”
Section: Catalysts -Carriers (Generators) Of the Active Factor Of Cat...mentioning
confidence: 99%
“…Since the field-induced change on regioselectivity in Diels–Alder (DA) reactions predicted by Shaik and co-workers was experimentally validated, this chemistry is becoming more tangible and there has been a reborn of the topic also from the theoretical perspective . Additionally, examples of the application of EEF on very diverse topics as the tuning of photo- and excited-state chemistry, switch molecular diodes, quantum tunneling, and homo- and heterogeneous catalysis have been successfully investigated. , …”
Section: Introductionmentioning
confidence: 99%
“…10−12 Using an external field, the rate of the ultracold chemical reactions could be tuned by varying the field strength. 13 The use of oriented external electric fields has opened new scientific possibilities such as the controlled modulation of molecular reactivity 14,15 and selective catalysis of single-molecule reactions. 16 Here, we demonstrate that it is possible to manipulate the molecular aggregation process of polar molecules at ultracold temperatures just by using an internal electric field created by a single molecular dipole, e.g., HCl.…”
mentioning
confidence: 99%
“…The strong external static electric field allows laser-induced one-dimensional alignment of state-selected polar molecules, offering new opportunities in molecular science. Using an external field, the rate of the ultracold chemical reactions could be tuned by varying the field strength . The use of oriented external electric fields has opened new scientific possibilities such as the controlled modulation of molecular reactivity , and selective catalysis of single-molecule reactions …”
mentioning
confidence: 99%